Epidemiological characteristics of carbapenemase-producing outbreaks in the Republic of Korea between 2017 and 2022 - Hyoseon Jeong; Junghee Hyun; Yeon-Kyeng Lee (Osong Public Health and Research Perspectives, 2023)
Objectives We aimed to describe the epidemiological characteristics of carbapenemase-producing Enterobacteriaceae (CPE) outbreaks in healthcare settings in the Republic of Korea between 2017 and 2022. Methods Under the national notifiable disease surveillance system, we obtained annual descriptive statistics regarding the isolated species, carbapenemase genotype, healthcare facility type, outbreak location and duration, and number of patients affected and recommended interventions. We used epidemiological investigation reports on CPE outbreaks reported to Korea Disease Control and Prevention Agency from June 2017 to September 2022. Results Among the 168 reports analyzed, Klebsiella pneumoniae (85.1%) was the most frequently reported species, while K. pneumoniae carbapenemase (KPC, 82.7%) was the most common carbapenemase genotype. Both categories increased from 2017 to 2022 (p<0.01). General hospitals had the highest proportion (54.8%), while tertiary general hospitals demonstrated a decreasing trend (p<0.01). The largest proportion of outbreaks occurred exclusively in intensive care units (ICUs, 44.0%), and the frequency of concurrent outbreaks in ICUs and general wards increased over time (p<0.01). The median outbreak duration rose from 43.5 days before the coronavirus disease 2019 (COVID-19) pandemic (2017–2019) to 79.5 days during the pandemic (2020–2022) (p=0.01), and the median number of patients associated with each outbreak increased from 5.0 to 6.0 (p=0.03). Frequently recommended interventions included employee education (38.1%), and 3 or more measures were proposed for 45.2% of outbreaks. Conclusion In the Republic of Korea, CPE outbreaks have been consistently dominated by K. pneumoniae and KPC. The size of these outbreaks increased during the COVID-19 pandemic. Our findings highlight the need for continuing efforts to control CPE outbreaks using a multimodal approach, while considering their epidemiology.